Pendampingan Pengisian Data SINTA dan SISTER bagi Para Dosen di Lingkungan STAI Hasan Jufri Bawean - Shobri, Muwafiqus; Hafidz, Abdul; M, Ansharuddin (PT. Cahya Edupreneur Indonesia, 2024)
This Community Service Program (CSP) aims to enhance the skills of lecturers at STAI Hasan Jufri Bawean in entering data into SINTA (Science and Technology Index) and SISTER (Integrated Resource Information System). The background of this activity highlights the importance of accuracy and completeness of data on these platforms for supporting academic careers and institutional reputation. The primary issue addressed is the lack of understanding and skills among lecturers in managing data on SINTA and SISTER and publication strategies for lecturers' work. The program is designed to provide technical assistance and education through three main methods: Socialization and Education, Technical Training, and Individual Assistance. Socialization involves seminars and interactive discussions to improve lecturers' understanding of the significance of both platforms. Technical training includes practical workshops and data entry simulations, while individual assistance offers direct support to address specific challenges. The results of this activity indicate a significant improvement in lecturers' understanding and skills, as well as an enhancement in the quality and accountability of the data produced. For continued effectiveness, it is recommended to implement periodic evaluations and monitoring, as well as a sustainable assistance system.